Suppression of in vitro monoclonal human rheumatoid factor synthesis by antiidiotypic antibody. Target cells and molecular requirements. - Koopman, W J (1983)
Previous studies have indicated that antiidiotypic antibody can modulate expression of idiotype both in vivo and in vitro. Although the precise mechanisms underlying modulation of idiotype expression by antiidiotype remains unclear, a requirement for intact IgG antiidiotypic antibody has been suggested and T cells appear to play a role in some systems. We have studied peripheral blood mononuclear leukocytes (MNL) from a patient with a B cell lymphoma and a circulating IgMK rheumatoid factor (RF) paraprotein in an effort to delineate mechanisms involved in regulation of idiotype expression by antiidiotypic antibody. 1-10% of MNL from this patient could be cytoplasmically stained with specific F(ab')2 antiidiotypic antibody. MNL from the patient spontaneously synthesized IgM RF in culture that possessed the same idiotype as the circulating IgM RF paraprotein. Production of RF by MNL was suppressed by pretreatment with either intact IgG or the F(ab')2 fragments of antiidiotypic antibody (50% inhibitory concentration was 0.2 and 1.1 micrograms/culture, respectively). In contrast, the Fab' fragment of antiidiotypic antibody was not inhibitory (up to 57 micrograms/culture) despite retaining demonstrable antiidiotype activity. Suppression of RF production was not observed over the same concentration range with the IgG or F(ab')2 fractions of a non-cross-reactive antiidiotypic antibody prepared against another monoclonal IgMK RF paraprotein or with IgG or F(ab')2 fractions prepared from normal rabbit serum. Inhibition of RF production by antiidiotypic antibody did not require T cells. Antiidiotypic antibody decreased intracellular and extracellular levels of idiotype indicating diminished synthesis of idiotype by the patient's B cells. Synthesis of IgM RF by MNL obtained from unrelated donors was not suppressed by the antiidiotypic antibody specific for the patient's paraprotein. The results indicate that (a) antiidiotypic antibody is capable of directly suppressing human B cell release of idiotype, (b) the bivalent antigen-binding fragment (F[ab']2) of antiidiotypic antibody is sufficient for mediating such suppression, (c) an intact Fc portion of antiidiotypic antibody enhances suppression of idiotype, and (d) antiidiotypic antibody inhibits idiotype expression by suppressing synthesis of idiotype.